2021
DOI: 10.21511/ee.12(1).2021.04
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gap in enterprise access to renewable energy between rural and urban areas in Cameroon

Abstract: Permanent access to energy is an essential pillar of economic development. However, there is a growing evidence that contemporary energy systems are not able to provide energy to the entire population on a sustainable basis and at affordable prices. In the face of these challenges, renewable energy can play an important role, especially in rural areas where access to centralized electricity grids is difficult. This paper aims to examine the access gaps of enterprises to renewable energy between rural and urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This study revealed that urban households are likelier to adopt cleaner fuels than their counterparts. It is similar to previous studies conducted in Cameroon 41 . In developing countries, impoverished urban households rely on solid fuels for cooking due to insufficient supplies, high costs of clean fuels and limited access to clean energy, as highlighted by various studies 34 , 35 , 42 .…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that urban households are likelier to adopt cleaner fuels than their counterparts. It is similar to previous studies conducted in Cameroon 41 . In developing countries, impoverished urban households rely on solid fuels for cooking due to insufficient supplies, high costs of clean fuels and limited access to clean energy, as highlighted by various studies 34 , 35 , 42 .…”
Section: Discussionsupporting
confidence: 92%
“…Earlier studies aimed to study aspects of labor migration (Přívara & Trnovský, 2021), rural-urban migration (Bodjongo et al, 2021), and forced migration due to war (Nikolaiets et al, 2023). A clear pattern can be traced from the previously cited studies -an emphasis on the consequences and of isolation in the groups of IDPs themselves (Kupenko et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high variability of daily business of power grid enterprises, this time, it is necessary to add the management idea of "implementing step by step and reaching the standard in sections" [13] on the original basis. Step by step, establish a complete management process and system, realize the closed-loop control of the whole digital life cycle, and ensure the unity of management objectives [14] . However, it should be noted that the current life cycle management idea is not fixed, but can be adjusted with the actual operation status and development management needs of power grid enterprises, and it has strong stability and reliability [15] .…”
Section: Design Life Cycle Management Ideasmentioning
confidence: 99%